The role of organisational capability mediates the relationship between external and internal support on SMEs performance - Yap, Luen Her (2020)
The purpose of this study is to examine the relationship between external support, internal support and firm performance mediated by organisational capability among SMEs in Malaysia. Organisational capability represent the firms' ability of coordination and deployment of resources. This study intends to identify the link between the support dimensions that which include the government support, financial capital support, ICT support and entrepreneurial orientation support on the business performance which mediated by organisational capability. This study was used stratified random sampling techniques to select the sample. The researcher uses multiple approaches to distribute questionnaires to the selected 384 respondents. A sample size of 296 respondents were collected which then analysed with descriptive analysis, validity analysis, reliability analysis, Pearson correlation analysis, multiple linear regression analysis, simple linear analysis, and hierarchical regression analysis approach. The data analysed by using the 'Statistical Package for Social Sciences' SPSS version 22. Collectively, the results showed that the financial capital support, JCT support and entrepreneurial orientation support presented a positive relationship with business performance by using the multiple regression analysis. However, the finding showed that the government support has negative relationship with business performance. Furthermore, this study applied the Baron and Kenny (1986) hierarchical regression analysis in examining the mediation effect which is organisational capability. The findings showed that the organisational capability is partial mediator of the relationship between government support, financial capital support and business performance but organisational capability become the full mediating role in the relationship between !CT support, entrepreneurial orientation support and business performance. This study tests the mediating role of organisational capabilities between external support, internal support and organizational performance with the help of resource-based view and contingency theory.